Children and Practitioners as Truth Seekers and Truth Tellers: Innovative, Counter-Hegemonic Approaches to Evaluating National Inclusion Policies - Deborah Robinson; Geraldene Codina (MDPI AG, 2024)
This paper describes and defends the counter-hegemonic methods applied to the investigation of a high-profile national policy for Early Education and Care (ECCE) in Ireland. The policy, the Access and Inclusion Model (AIM) seeks to ensure the full inclusion and meaningful participation of children with disabilities in mainstream, state funded ECCE. It makes a significant contribution to data and debate on how research about inclusion can become inclusion in the context of policy evaluation. The design of the policy evaluation included surveys, in depth interviews and qualitative case studies of pre-schools and children supported by AIM which were deliberately designed to be counter-hegemonic through the recruitment of practitioners as co-researchers (as expert representatives within a feminised workforce), and the use of a participative method of elicitation that sough the perspectives and lived experiences of inclusion among fourteen children supported by AIM. This method was multi-modal mapping. With a focus on these counter-hegemonic elements, the paper poses questions about how the approach was counterhegemonic in terms of its theoretical underpinning, practical approach, and outcomes. Thematic analysis of the data collected by practitioner researchers for the child case studies showed that the approach did achieve counter-hegemony through the achievement of redistribution, representation, and recognition in both the enactment of the research, and in the reporting of children's lived experience in the study as a whole. However, the extent of counter-hegemony achieved was limited when practitioner researchers were unable to deploy the multi-modal mapping method because of limited time, or because the child was not a speaker of English or was as yet, non-speaking. In a context where policy makers have a preference for positivist and rationalist approaches to evaluating the impact of policies, we assert that research about policies for inclusion, should be enacted as inclusion and social justice through the deliberate deployment of participatory and counter-hegemonic methods. We also assert that multi-modal mapping holds particular promise for researching the lived experience of inclusion and participation from the perspective of children and argue that more work needs to be done on developing these methods so that they are effective with all children, including those who are non-speaking. Finally, we posit that Fraser's triune model of social justice can be applied as a benchmark for designing and evaluating counter-hegemonic modii and outcomes.